Complete pathologic response to short-course neoadjuvant alectinib in mediastinal node positive (N2) ALK rearranged lung cancer. (October 2022) - Sentana-Lledo, Daniel; Viray, Hollis; Piper-Vallillo, Andrew J.; Widick, Page; Rangachari, Deepa; Wilson, Jennifer L.; Gangadharan, Sidharta P.; Aronovitz, Joseph A.; Berman, Stuart M.; VanderLaan, Paul A.; Costa, Daniel B.
Highlights: Neoadjuvant therapy prior to surgical resection for locally advanced lung cancer has evolved to incorporate systemic cytotoxic chemotherapy +/- immunotherapy +/- radiotherapy. The role of neoadjuvant precision therapies remains understudied in ALK rearranged lung cancer. We report two cases of ALK rearranged stage III lung adenocarcinomas with a complete pathological response (ypT0 ypN0) and a major pathologic response (ypT1a ypN0) to neoadjuvant alectinib plus post-operative outcomes. These cases highlight the ability of ALK inhibitors to induce major and complete pathologic responses in the neoadjuvant setting plus the likely role of long-term adjuvant kinase inhibitor therapy to prevent radiographic/clinical recurrence. Abstract: Objectives: Neoadjuvant therapy prior to surgical resection for locally advanced lung cancer has evolved to incorporate systemic cytotoxic chemotherapy +/- immunotherapy +/- radiotherapy. The role of neoadjuvant precision therapies remains understudied. Materials and Methods: We report cases with major and complete pathologic responses to off-label neoadjuvant alectinib. Results: A case with stage IIIA (cT1b cN2 cM0) EML4 - ALK variant 3a/b lung adenocarcinoma received 6 weeks of alectinib followed by R0 left upper lobectomy with complete pathological response (ypT0 ypN0). Another case with stage IIIA (cT3 cN2 cM0) EML4 - ALK variant 2 received 12 weeks of alectinib followed by R0 right middle lobectomy with a major pathologic response (ypT1a ypN0) but systemic recurrence 12 months post-operatively. Conclusion: Ongoing clinical trials are evaluating the role of both neoadjuvant and adjuvant ALK-directed therapy. Our cases support the completion of ongoing trials (ALINA: NCT03456076 and ALNEO: NCT05015010), and highlight the ability of second generation ALK inhibitors to induce major and complete pathologic responses in the neoadjuvant setting plus the likely role of long-term adjuvant kinase inhibitor therapy to prevent radiographic/clinical recurrence.